“Lending a hand”: the well-intentioned work of a non-profit organisation on the outskirts of neoliberal Lisbon - Catela, J. (International Journal of Human Rights in Healthcare, 2019)
Purpose – The purpose of this paper is to focus on the mental health of two immigrants supported by a non-profit organisation on the outskirts of Lisbon. The ethnography sets out the discourse of these users who are also residents of Terraços da Ponte, a social housing neighbourhood, and the workers who try to help them in the context of the non-profit organisation’s endeavours. Design/methodology/approach – In order to explore the intersections between these users and state and non-state structures, this investigation relied on intensive fieldwork at a rehabilitated neighbourhood in Lisbon, as well as semi-directive interviews and life stories taken with workers of the institution and the people they were trying to help. Findings – This paper shows how vulnerability has been produced in a social housing neighbourhood on the outskirts of Lisbon and how it connects to neoliberal policies employed by NGOs acting on the field. Research limitations/implications – Any general conclusions about the subject need to take into consideration that this research looks at the work of a specific non-profit organisation during a particular period in time. Practical implications – This research seeks not only to promote a critical approach to the subject, but also to contribute to the production of appropriate health policies for the immigrant population residing in Portugal. Originality/value – The analysis of health and social care practices regarding so-called vulnerable subjects relies heavily on “a mix of good intentions, developmental ambitions, paternalistic attitudes and desire to control deviant populations” (Pussetti and Barros, 2012, p. 47). Although there is not a single solution to this problem, several levels of analysis were explored: the non-profits’ goals and inspirations, the workers motivations, the subjects’ expectations regarding the kind of help they can get from these services and their ability to exert their own agency despite the conditions governing their lives.